Key value drivers throughout business life cycle - Saller, Andriy; Zárybnická Žárová, Marcela, 1959-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2019)
This research master’s thesis adapts the concept of business life cycle as the basis for valuation ofany company. Main characteristics, valuation approaches and methods for start-up, high-growth,mature and declining companies are discussed in order identify key drivers determining the firmvalue. Case study valuations are conducted for Qover, Netflix, Microsoft, and General Electric toprovide empirical evidence for the impact of key value drivers at each stage of business life cycle.
Vedoucí práce: Marcela Zárybnická Žárová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses